2022
DOI: 10.1111/dth.15852
|View full text |Cite
|
Sign up to set email alerts
|

Wet‐wrap therapy combined with compound glycyrrhizin and oral antihistamines as a therapy option for two cases of papuloerythroderma of ofuji

Abstract: Papuloerythroderma of Ofuji (PEO) is a rare erythroderma with "deckchair" sign, and there is no specific treatment yet. Here, we present two cases of PEO, which are responsive to wet-wrap therapy (WWT) combined with Compound Glycyrrhizin and oral antihistamines.Case one, a 72-year-old Chinese male who had generalized pruritic rashes for 1 month. He had cerebrovascular stenosis for 4 years.Dermatological examination showed a wide range of erythema, covering more than 80% of the body surface, which was character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…After remove of duplicates, title and abstract screening, and full-text assessment, 39 eligible RCTs enrolling 3994 participants with vitiligo were evaluated in our meta-analysis. [26–64] The selection process is shown in Figure 1. The included trials were carried out in China and published in the Chinese language from 2005 to 2021, except one published in English.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After remove of duplicates, title and abstract screening, and full-text assessment, 39 eligible RCTs enrolling 3994 participants with vitiligo were evaluated in our meta-analysis. [26–64] The selection process is shown in Figure 1. The included trials were carried out in China and published in the Chinese language from 2005 to 2021, except one published in English.…”
Section: Resultsmentioning
confidence: 99%
“…A meta-analysis including 7 trials [47][48][49][50][51][52][53] revealed that combination therapy of CG and TCM was better than TCM alone in terms of repigmentation > 50% (RR = 1.38, 95% CI: 1.21-1.57, P < .001), there was no heterogeneity (I 2 = 0%), as shown in Figure 5.…”
Section: Add-on Effect Of Cg To Other Tcmmentioning
confidence: 99%